The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.15376/biores.9.1.316-335
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Community Structure and Biochemical Changes Associated With Composting of Lignocellulosic Oil Palm Empty Fruit Bunch

Abstract: Bacterial community structure and biochemical changes during the composting of lignocellulosic oil palm empty bunch (EFB) and palm oil mill effluent (POME) anaerobic sludge were studied by examining the succession of the bacterial community and its association with changes in lignocellulosic components by denaturing gradient gel electrophoresis (DGGE) and the 16S rRNA gene clone library. During composting, a major reduction in cellulose after 10 days from 50% to 19% and the carbon content from 44% to 27% towar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
3
11
0
Order By: Relevance
“…Analysis of the bacterial community structure at the levels of phylum and order by shotgun DNA as well as by 16S rRNA gene amplicon sequencing yields two main results: 1) shotgun DNA and 16S amplicon results by and large agree with each other; 2) the phyla and orders that are most abundant agree with those found in previous studies14789101112. The four most abundant phyla throughout the composting process are Firmicutes, Proteobacteria, Bacteroidetes and Actinobacteria (Supplementary Fig.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Analysis of the bacterial community structure at the levels of phylum and order by shotgun DNA as well as by 16S rRNA gene amplicon sequencing yields two main results: 1) shotgun DNA and 16S amplicon results by and large agree with each other; 2) the phyla and orders that are most abundant agree with those found in previous studies14789101112. The four most abundant phyla throughout the composting process are Firmicutes, Proteobacteria, Bacteroidetes and Actinobacteria (Supplementary Fig.…”
Section: Resultssupporting
confidence: 80%
“…The biological decomposition of organic matter is performed by mesophilic and thermophilic microbial consortia with distinct physiological requirements and tolerances, consistent with the continuously changing environment throughout composting34567. Bacterial phyla including Proteobacteria, Firmicutes, Bacteroidetes and Actinobacteria are routinely found in composting, being more or less abundant depending on the starting materials and the composting procedure14789101112. Generally, fungi are not detected in composting piles above 65 °C, suggesting that their degradative activities during the thermophilic stages of composting are minor compared to that of bacteria1314.…”
mentioning
confidence: 98%
“…The results suggested that the highest value for degradation rate, OM loss and lowest final C/N were obtained by using periodic addition of sludge compared to the addition of only water and no addition at all regardless of the initial C/N ratio of the different experiments. The results obtained agreed with those of the previous work carried out by Mohd Zainudin et al (2014) and Wan Razali et al (2012). Clearly, as expected, periodic addition of sludge allowed the organic matter loss increase to justify addition not only for moisture content regulator but supporting nutrient needs for microbial to grow.…”
Section: Resultssupporting
confidence: 90%
“…In spite of all this potential, knowledge on how to control and explore those microbes and their functions remains encrypted within their genomes and the multiple combinations of metabolic pathways that they can activate [7][8][9]. So far, research on composting microbes has focused mainly on enriched cultures [9][10][11] or taxonomic biodiversity assessments based on 16S rRNA gene amplicon sequencing data [12,13]. Enriched cultures have lower diversity richness due to cultivation bias and the limited number ecological niches [9].…”
Section: Introductionmentioning
confidence: 99%